A Study On Consumer Adoption Towards 3G Service In Malaysia - Govindasamy, Naveena (2006)
The study was undertaken to evaluate the factors that encourage the usage of 3G services in Malaysia. This paper concludes that consumer adoption of 3G services has a potential to progress to greater scales of height despite the current slow growth.